The Ukraine crisis and control of weapons of mass destruction: Impacts on German arms control objectives - Oliver Meier (Stiftung Wissenschaft und Politik (SWP), 2014)
Russia's annexation of Crimea will make it harder for Germany to achieve its disarmament and non-proliferation objectives. Joint action by Russia and the United States to reduce their strategic nuclear arsenals appears unlikely in the medium term. And that reduces the chances of tactical nuclear weapons being included - as Germany would prefer - in a future arms control accord. While existing nuclear arms control agreements have not thus far been openly called into question, they may yet become consumed by the ongoing Ukraine crisis. Berlin should argue against NATO re-directing missile defences at a Russian threat. In order to prevent a further weakening of the nuclear non-proliferation treaty, Germany can emphasise the value of security guarantees for non-nuclear-weapon states. (SWP Comments)
Keywords: 320